Generation Z and Legal Literacy: Efforts to Increase Understanding of Human Rights by Digital World - Yudith Sitinjak; Dani Hiskia Siringo-ringo (Jurnal Multidisiplin Sahombu, 2025)
The digital era brings new challenges in understanding and protecting human rights, especially for Generation Z who grew up in a digital environment. Legal literacy becomes key to providing an in-depth understanding of human rights and ways protecting them in the digital world. This article discusses the importance of legal literacy for Generation Z. in supporting awareness and protection of human rights. By using descriptive-qualitative approach, this article explores the role of legal literacy in improve Generation Z's understanding of their human rights, as well as provide recommendations strategies for integrating legal literacy into formal and non-formal education.